Mixed formulation for navier stokes equations - Rawi, Mohd. Rosdi (2014)
This dissertation presents the formulation and numerical computation of the two dimensional fluid flow whose physics is governed by the Navier Stokes equations. The derivation of the governing equations follows the model of an infinitesimally small element fixed in space with the fluid moving through it. The study focuses using finite element method for solving the fluid flow. Finite element method is believed as the most powerful numerical method for analysis. Mixed formulation has been used for the discretization of the governing equations. It is because we have two primitive variables; velocities and pressure. Source code for Navier Stokes equations has been developed and tested against existing benchmark solutions.